O discurso gerencialista na educação paulista: uma análise crítica do discurso de Renato Feder à luz da Teoria Crítica - Bandeira, Thaise Proença (Universidade Federal de São Carlos, 2026)
This research analyzes the public discourses on education by Renato Feder, Secretary of Education of the State of São Paulo, in order to reveal their managerialist bases and how they operate ideologically. The study builds on the premise that the dissemination of managerialism promotes a progressive colonization of public education by corporate principles, which naturalizes market logic and reduces complex educational issues to mere technical dimensions. It investigates, therefore, to what extent these managerial bases express the contemporary dynamics of semi-formation and the “new spirit” of capitalism. To ground the critique, the framework anchors itself in the Critical Theory of Society, mobilizing the concepts of Culture Industry, formation (Bildung), and semi-formation (Halbbildung) described by Theodor W. Adorno and Max Horkheimer, articulated with the formulations of Luc Boltanski and Ève Chiapello regarding the transformations and justifications of contemporary capitalism. From a methodological standpoint, it adopts Critical Discourse Analysis (CDA) from Norman Fairclough’s perspective, investigating discourse in its textual, discursive practice, and social practice dimensions. The source material gathers two primary sources: the book Educação para o future (Feder, 2023) and the lecture Atuais desafios da educação, delivered by the secretary in November 2025. The results of the analysis are structured around four fundamental axes: the construction of the manager’s discursive legitimacy; the conception of education as management focused on quantifiable goals and results; the relationship between technology and semi-formation through the platformization and monitoring of teaching; and the construction of the desirable subject aligned with corporate and capital demands. It concludes that the discourse closely approaches the notion of the “new spirit of capitalism” by articulating justifications for promoting the incorporation of the logic of capital into the subjects, as well as produces semi-formation by impoverishing the emancipatory character of the school under the guise of modernization.
Managerialist discourse in São Paulo education: a critical analysis of Renato Feder's discourse in light of Critical Theory
Keywords: Gerencialismo; Teoria crítica; Análise crítica do discurso; Semiformação; Novo espírito do capitalismo; New management ideology; Critical theory; Critical discourse analysis; Semiformation; New spirit of capitalism; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade; 10. Redução das Desigualdades